2016
DOI: 10.1016/j.polymer.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of ion-induced cross-linked sulfonated poly(ether ether ketone)

Abstract: The dehydration of SPEEK-[H] (protonated sulfonated poly(ether ether ketone)) converts 3-fold symmetric (C 3V) hydrated sulfonate sites to sulfonic acid sites with no local symmetry (C 1). Like Nafion-[H], SPEEK-[H] C 3V and C 1 environments afford IR group modes (C 3V,HF (1087 cm-1); C 3V,LF (1026 cm-1) and C 1,HF (1362 cm-1); C 1,LF (904 cm-1)) due to the mechanical coupling of vibrational internal coordinates of an ether link with those of the sulfonate or sulfonic acid exchange site. C 3V and C 1 bands are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…These assignments are further supported by augmenting eigenvector animations (SI Video 1–28) with experimental spectra obtained by altering the exchange site environment (e.g., state of hydration, ion speciation, derivatization of the ionomer, etc. ). , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These assignments are further supported by augmenting eigenvector animations (SI Video 1–28) with experimental spectra obtained by altering the exchange site environment (e.g., state of hydration, ion speciation, derivatization of the ionomer, etc. ). , …”
Section: Resultsmentioning
confidence: 99%
“…Infrared (IR) and Raman spectroscopy, correlated to density functional theory (DFT) calculated normal-mode analyses, facilitate characterization of the PFSI exchange site environment versus state of hydration. , DFT, a quantum mechanical description of electronic, structural, and vibrational properties of molecular and crystalline systems, is based on the Hohenberg and Kohn theorems. The total system energy is a functional of electron density. The exact ground state may be obtained if this functional is known.…”
Section: Introductionmentioning
confidence: 99%
“…29 It is confirmed that the introduction of sulfonic acid group did not change the basic structure of PEEK, and PEEK has been successfully sulfonated. 30 Figure 2 shows the SEM image and energy spectrum (EDS) of PEEK and SPEEK. It can be seen from Figure 2(a) that PEEK structure is tight within a certain range and there are a little holes, Figure 2(c) demonstrates the microcosmic morphology of SPEEK, which is quite different from PEEK.…”
Section: Microstructure Of Peek Speek and Pesmentioning
confidence: 99%
“…[6][7][8] Sulfonated poly(ether ether ketone) (SPEEK) is a PEM that can potentially be applied for DMFCs as SPEEK exhibits high proton conductivity, good mechanical properties, and low-cost production. [9][10][11] However, proton conductivity depends on the degree of sulfonation (DS). SPEEK membranes prepared at high DS have poor dimensional stability, high methanol diffusion, and low mechanical properties.…”
Section: Introductionmentioning
confidence: 99%